Immunological Aspects of Intrauterine Infection in Newborns - Zarifovna, Omonova Guzal (Journal of Science in Medicine and Life, 2024)
Intrauterine infection (IUI) is the main cause of death in 37.5% of newborns or is a complication of the course of the main disease, and occupies one of the leading positions in the structure of neonatal death. There is no reliable data on the actual prevalence of IUI. However, according to a number of studies, infectious diseases are detected in 50-60% of full-term hospitalizations and 70% of premature babies [1]. The main cause of IUI is infectious urogenital diseases of the mother, the frequency of which has remained high among pregnant women in the last 10 years and is 88-100 per 1000 pregnant women. Unfortunately, at the moment we do not have reliable information about the probability of the fetus being infected from an infected mother, but the risk of infection of the fetus with various microorganisms isolated from the mother is from 5 to 70%, data on frequency. The prevalence of infection in newborns is insufficient and highly contradictory [2, 3].